The implementation of socio-economic development strategies in the country contributes to an increase in the efficiency of human capital - Ubaydullayev Gayrat Zuvaytovich (THE INNOVATION ECONOMY, 2026)
The aim of the study is to analyze practical work aimed at improving the education of individuals, knowledge, skills, abilities, motivation, career guidance, science, healthcare and culture for the development of human capital in New Uzbekistan, as well as to study the methodological, theoretical and practical foundations of the factors for the development of human capital effectiveness in the implementation of strategies for the socio economic development of the country